Clinical features and FLAIR radiomics nomogram for predicting functional outcomes after thrombolysis in ischaemic stroke - Xu, Qingqing; Zhu, Yan; Zhang, Xi; Kong, Dan; Duan, Shaofeng; Guo, Lili; Yin, Xindao; Jiang, Liang; Liu, Zaiyi; Yang, Wanqun (Frontiers in Neuroscience, 2023)
Abstract: Objective: We explored whether radiomics features extracted from diffusion-weighted imaging (DWI) and fluid-attenuated inversion recovery (FLAIR) images can predict the clinical outcome of patients with acute ischaemic stroke. This study was conducted to investigate and validate a radiomics nomogram for predicting acute ischaemic stroke prognosis. Methods: A total of 257 patients with acute ischaemic stroke from three clinical centers were retrospectively assessed from February 2019 to July 2022. According to the modified Rankin scale (mRS) at 3 months, the patients were divided into a favourable outcome group (mRS of 0-2) and an unfavourable outcome group (mRS of 3-6). The high-throughput features from the regions of interest (ROIs) within the radiologist-drawn contour by AK software were extracted. We used two feature selection methods, minimum redundancy and maximum (mRMR ) and the least absolute shrinkage and selection operator algorithm (LASSO), to select the features. Three radiomics models (DWI, FLAIR and DWI-FLAIR) were established. A radiomics nomogram with patient characteristics and radiomics signature was built using a multivariate logistic regression model. The performance of the nomogram was evaluated in the test and validation sets. Ultimately, decision curve analysis was implemented to assess the clinical value of the nomogram. Results: The FLAIR, DWI and DWI-FLAIR radiomics model exhibited good prediction performance, with area under the curve (AUCs) of 0.922 (95% CI: 0.876-0.968), 0.875 (95% CI: 0.815-0.935) and 0.895 (95% CI: 0.840-0.950). The radiomics nomogram with clinical characteristics including the overall Cerebral small vessel disease (CSVD) burden score, hemorrhagic transformation(HT) and admission National Institutes of Health Stroke Scale score (NIHSS) score and the FLAIR Radscore presented good discriminatory potential in the training set（AUC=0.94; 95% CI：0.90-0.98）and test set（AUC=0.94; 95% CI：0.87-1）, which was validated in the validation set 1(AUC=0.95; 95% CI 0.88-1) and validation set 2(AUC=0.90; 95% CI 0.768-1). In addition, it demonstrated good calibration, and decision curve analysis confirmed the clinical value of this nomogram. Conclusion: This noninvasive clinical-FLIAR radiomics nomogram shows good performance in predicting ischaemic stroke prognosis after thrombolysis.